Epidemiology of Psoriasis in Portugal: A Population-Based Study - Torres, T; Filipe, P; Menezes Brandão, F; Figueiredo, A; Pinto Soares, A; Sousa Basto, A; Rebelo, C; Correia, O; Ferreira, P; Brasileiro, A; Mendes-Bastos, P; Paiva-Lopes, MJ; et al. (My University, 2023)
Introduction: Psoriasis is a common, chronic, and inflammatory skin disorder with a high personal, social and economic burden and important implica-tions for healthcare systems. The aim of this study was to provide an epidemiological characterization of individuals with psoriasis in Portugal.Material and Methods: A large observational, cross-sectional, nationwide, population-based survey study developed by the Portuguese Psoriasis Group of the Portuguese Society of Dermatology and Venereology (GPP-SPDV). A structured questionnaire was designed and applied by experienced inter-viewers to a random, representative sample of Portuguese individuals with psoriasis and/or psoriatic arthritis. Patients were considered to have psoriasis if they replied positively to one of the following questions: “Does any physician have ever diagnosed you with psoriasis?” or “Do you have a skin disorder characterized by scaling, reddish skin lesions located in the elbows/knees/scalp?”.Results: A total of 6381 individuals were interviewed, of which 283 met the criteria for psoriasis, corresponding to a prevalence rate of 4.4% (95% CI 3.95 – 4.98). Out of the participants that met psoriasis criteria, 24% had suggestive signs/symptoms but did not have a clinical diagnosis established and were not being monitored by a physician. Although more than 70% of participants had active disease (scaling, erythema, or pruritus) and one third had joint symptoms, only 12% were on systemic treatment. Fifty percent of participants with psoriasis (n = 139) had relevant comorbidities (most frequently depression/anxiety and cardiometabolic diseases). Sixteen percent of participants with psoriasis (n = 46) reported that psoriasis interfered with their daily activities (median impact of 5 in a 0 – 10 scale) and 12% mentioned the disease had an impact in their sexual life (median impact of 5 in a 0 – 10 scale). Conclusion: The results of this study suggest that the prevalence rate of psoriasis is likely to be high in Portugal, and several gaps exist at different levels of healthcare delivery to these patients, from diagnosis to treatment. This study provides important data for the future planning of interventions targeting the improvement of psoriasis care in Portugal.
Epidemiologia da Psoríase em Portugal: Um Estudo de Base Populacional
Keywords: Arthritis, Psoriatic/epidemiology; Psoriasis/epidemiology; Surveys and Questionnaires; Artrite Psoriática/epidemiologia; Inquéritos e Questionários; Psoríase/epidemiologia